The Brain's Heterogeneous Functional Landscape. - McCaffrey, Joseph B. (Philosophy of Science, 2015)
Multifunctionality poses significant challenges for human brain mapping. Cathy Price and Karl Friston argue that brain regions perform many functions in one sense and a single function in another. Thus, neuroscientists must revise their "cognitive ontologies" to obtain systematic mappings. Colin Klein draws a different lesson from these findings: neuroscientists should abandon systematic mappings for context-sensitive ones. I claim that neither account succeeds as a general treatment of multifunctionality. I argue that brain areas, like genes or organs, are multifunctional in different ways. I call this the "functional heterogeneity hypothesis." I contend that different multifunctional parts require different mapping strategies.